Characterization of Vacuolar Calcium-Binding Proteins - Randall, Stephen K. (1992)
The vacuole plays a major structural and biochemical role in the higher plant cell. Among the most studied properties of the vacuole have been transport activities. One important aspect of vacuolar function is its participation in the regulation of cytosolic calcium levels. To identify the molecular entities involved in calcium regulation, a study of vacuole-associated, calcium-binding proteins (CaBs) was initiated. A competition assay was used, and it was observed that the majority of the total cellular membrane-associated, calcium-binding activity resided in low-density fractions enriched in vacuole membranes. Much of that calcium-binding activity was inactivated by a 0.5 m KI wash, and of the remaining activity, 77% was estimated to be peripherally associated with vacuolar membranes, whereas 23% was integrally associated with the vacuolar membrane. Calcium-ligand blots were used, and four major CaBs, with apparent molecular masses of 64, 58, 55, and 42 kD, were detected in purified vacuole membrane fractions. Two of these, the 58- and the 55-kD polypeptide, also appear to be present in significant amounts in endoplasmic reticulum-enriched fractions. However, the 64- and the 42-kD polypeptide are found primarily in vacuolar fractions. It is interesting that expression of the 42-kD polypeptide appears to be restricted to the heavily vacuolated cortical tissues (i.e. it is not found in vascular tissues). The localization of CaBs in the vacuole is consistent with the presence of calcium uptake (H(+)/Ca(2+) antiport) and release mechanisms (inositol trisphosphate sensitive) on vacuolar membranes. These vacuole-associated CaBs, which may play a role in calcium buffering, together with the calcium transport systems, could mediate the vacuolar component of cellular calcium homeostasis.